2010
DOI: 10.1128/mcb.01038-09
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of G-Protein Signaling by RKTG via Sequestration of the Gβγ Subunit to the Golgi Apparatus

Abstract: Upon ligand binding, G-protein-coupled receptors (GPCRs) impart the signal to heterotrimeric G proteins composed of ␣, ␤, and ␥ subunits, leading to dissociation of the G␣ subunit from the G␤␥ subunit. While the G␣ subunit is imperative for downstream signaling, the G␤␥ subunit, in its own right, mediates a variety of cellular responses such as GPCR desensitization via recruiting GRK to the plasma membrane and AKT stimulation. Here we report a mode of spatial regulation of the G␤␥ subunit through alteration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 35 publications
4
35
1
Order By: Relevance
“…The inhibitory activity of RKTG on Raf/MEK/ERK signaling has been reported in several tumor cell lines (11,12,14,15,20). Additionally, the activation of the PI3K/AKT signaling pathway induced by Gβlγ2 overexpression in monkey kidney fibroblast cells COS7 has been previously reported to be markedly abrogated by RKTG co-overexpression (28). The present study demonstrated that upregulation of RKTG significantly suppressed the activation of ERK and PI3K/AKT signaling pathways.…”
Section: Discussionsupporting
confidence: 74%
“…The inhibitory activity of RKTG on Raf/MEK/ERK signaling has been reported in several tumor cell lines (11,12,14,15,20). Additionally, the activation of the PI3K/AKT signaling pathway induced by Gβlγ2 overexpression in monkey kidney fibroblast cells COS7 has been previously reported to be markedly abrogated by RKTG co-overexpression (28). The present study demonstrated that upregulation of RKTG significantly suppressed the activation of ERK and PI3K/AKT signaling pathways.…”
Section: Discussionsupporting
confidence: 74%
“…RKTG can also regulate signalling through GPCRs by binding to the Gb subunit of heterotrimeric G proteins and by tethering Gb to the Golgi complex (Jiang et al, 2010). This recruitment impedes the interaction between Gb and b-adrenergic receptor kinase 1 (ARBK1, also known and hereafter referred to as GRK2), whose activation is crucial for the desensitisation of GPCRs, such as the b2-adrenergic receptor (ADRB2).…”
Section: Rktgmentioning
confidence: 99%
“…This recruitment impedes the interaction between Gb and b-adrenergic receptor kinase 1 (ARBK1, also known and hereafter referred to as GRK2), whose activation is crucial for the desensitisation of GPCRs, such as the b2-adrenergic receptor (ADRB2). Accordingly, overexpression of RKTG inhibits desensitisation of this receptor (Jiang et al, 2010). Gb also mediates ADRB2-induced activation of Akt, which itself is inhibited by RKTG overexpression (Jiang et al, 2010).…”
Section: Rktgmentioning
confidence: 99%
“…Progestin and adipoQ receptor family member III (PAQR3), also named RKTG, negatively regulates the Ras/Raf/MEK/ERK signaling cascade and the G protein-coupled receptor (GPCR) Gβγ subunit signaling pathway (8,9). PAQR3 is a member of the PAQR family of proteins comprising an intriguing group of recently discovered receptors and a seven transmembrane protein localized at the Golgi apparatus (8,10).…”
Section: Introductionmentioning
confidence: 99%